Peran Pemecahan Masalah Bagi Mahasiswa Tadris Matematika Untuk Meningkatkan Kemampuan Penalaran Matematis - Diyah Ayu Rizki Pradita; Moh. Atikurrahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
Mathematical reasoning is one of the reasons students need in understanding creatives ideas. One approach to further develop mathematical reasoning is to play problem solving. By using this approach, students are expected to be directly involved in formulating, managing, and solving their own problems without the intervention of others. So in this study intends to examine the role of problem solving in improving mathematical reasoning skills. In this study, Mix methods is an approach with a Quasi Experimental Design Method as a form of comparison design. The subjects used were the control class which received cpntional learning and the experimental class which received assistance with a problem solving approach. The research was conducted at Ibrahimy University in the odd semester of the 2020/2021 academic year. Data collection was carried out starting from observation, tests, interviews, and documentation. The analysis technique used is decriptive qualitative and quantitative with paired samples test. The result of the study showed a significance value of (0,003  0,05) that the role of problem solving can improves student’s mathematical reasoning abilities with massive, active, and creative use being the key in this method. Keywords: problem solving, mathematical reasoning